Solar Cells Theory, Materials and Recent Advances - Mourtada Elseman, Ahmed (IntechOpen, 2021)
Solar cell energy is the single most pressing issue facing humanity, with a more technologically advanced society requiring better energy resources. This book discusses technologies broadly, depending on how they capture and distribute solar energy or convert it into solar power. The major areas covered in this book are: • The theory of solar cells, which explains the conversion of light energy in photons into electric current. The theoretical studies are practical because they predict the fundamental limits of a solar cell. • The design and development of thin-film technology-based solar cells. • State of the art for bulk material applied for solar cells based on crystalline silicon (c-Si), also known as "solar grade silicon," and emerging photovoltaics.